2022
DOI: 10.1002/jbm4.10677
|View full text |Cite
|
Sign up to set email alerts
|

Definition of Normal Vertebral Morphometry Using NHANES‐II Radiographs

Abstract: A robust definition of normal vertebral morphometry is required to confidently identify abnormalities such as fractures. The Second National Health and Nutrition Examination Survey (NHANES-II) collected a nationwide probability sample to document the health status of the United States. Over 10,000 lateral cervical spine and 7,000 lateral lumbar spine X-rays were collected. Demographic, anthropometric, health, and medical history data were also collected. The coordinates of the vertebral body corners were obtai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 96 publications
0
7
0
Order By: Relevance
“…The reference range for this threshold is set based on research results for various races and ages [10,12,13,31]. However, in recent years, several studies have reported that vertebral body morphology differs based on race, [32][33][34] gender, [33] and age. [34] Additionally, several studies have shown slight vertebral body crushing even in relatively young people [21,35]; we believe that it is necessary to understand the reference range of vertebral body morphology across a wide range of generations, genders, and races, rather than solely focusing on the elderly population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reference range for this threshold is set based on research results for various races and ages [10,12,13,31]. However, in recent years, several studies have reported that vertebral body morphology differs based on race, [32][33][34] gender, [33] and age. [34] Additionally, several studies have shown slight vertebral body crushing even in relatively young people [21,35]; we believe that it is necessary to understand the reference range of vertebral body morphology across a wide range of generations, genders, and races, rather than solely focusing on the elderly population.…”
Section: Discussionmentioning
confidence: 99%
“…However, in recent years, several studies have reported that vertebral body morphology differs based on race, [32][33][34] gender, [33] and age. [34] Additionally, several studies have shown slight vertebral body crushing even in relatively young people [21,35]; we believe that it is necessary to understand the reference range of vertebral body morphology across a wide range of generations, genders, and races, rather than solely focusing on the elderly population. To apply these research results in clinical practice, rapid QM is necessary, which is enabled by the proposed software.…”
Section: Discussionmentioning
confidence: 99%
“…The spondylolisthesis index in Supplementary File S3 utilizes the endplate width ratio to mitigate endplate width discrepancies. NHANES-II vertebral morphology data can help identify abnormalities in morphology [10]. Considering factors like pelvic incidence may also be important when interpreting SPO [41,52].…”
Section: Discussionmentioning
confidence: 99%
“…Details of landmark placement can be found in Supplementary File S1, as proper placement is crucial for accurate SPO and disc measurements. Vertebral morphology based on these landmarks has been reported previously [10]. While specific software was used to obtain landmarks, the focus of this study was not on the software itself, as the landmarks are intended to be consistent with those used in prior research studies [11][12][13][14][15].…”
Section: Methodsmentioning
confidence: 99%
“…However, this technology was not the focus of the study, as artificial intelligence and machine learning methods have been developed for use in identifying vertebral landmarks by many researchers. (60)(61)(62)(63)(64) The details of landmark placement for this study have been documented previously (65) and are intended to be comparable to those in prior studies. It is anticipated that the landmark placement used for strain measurements in this study can be replicated by alternative methods, making the data valuable for other investigators utilizing alternative methods for obtaining landmarks.…”
Section: Methodsmentioning
confidence: 99%